2018
DOI: 10.1038/s41598-018-35322-6
|View full text |Cite
|
Sign up to set email alerts
|

OCT3 promoter haplotype is associated with metformin pharmacokinetics in Koreans

Abstract: Organic cation transporter 3 (OCT3) is expressed in various organs in humans and plays an important role in the transport of organic cations and drugs including metformin. In this study, we identified genetic variations of the OCT3 promoter and functionally characterized each variant by in vitro assays. Next, the association between the functional haplotype of the OCT3 promoter and pharmacokinetics of metformin was evaluated. In our study population, 7 variations and 2 major haplotypes were identified, of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Promoter mutations may contribute to the alteration of transcriptional activity, expression dose, and phenotypic characteristics [28,29]. Kwon et al found that the OCT3 promoter haplotype H2 significantly affected luciferase activity as well as the metformin pharmacokinetics [30]. Our previous study reported that the T-A haplotype of the CREB1 gene exhibited maximal promoter activity, and resulted in susceptibility to T2D [14].…”
Section: Discussionmentioning
confidence: 94%
“…Promoter mutations may contribute to the alteration of transcriptional activity, expression dose, and phenotypic characteristics [28,29]. Kwon et al found that the OCT3 promoter haplotype H2 significantly affected luciferase activity as well as the metformin pharmacokinetics [30]. Our previous study reported that the T-A haplotype of the CREB1 gene exhibited maximal promoter activity, and resulted in susceptibility to T2D [14].…”
Section: Discussionmentioning
confidence: 94%
“…SNPs of OCT3 significantly affect intestinal absorption of metformin [ 66 , 67 ], demonstrating important roles of OCT3 in intestinal absorption of metformin, and some reports have showed that PMAT, OCT1 and SERT are involved in metformin transport in Caco-2 cells and other cell lines [ 11 , 28 , 51 ]. Based on data from OCT3 knockout mice and cell lines, we assumed that contribution of intestinal OCT3 and PMAT to intestinal absorption of metformin was about 50% and 20%, respectively, the rest (30%) was attributed to other transporters including THTR2, OCT1 and maybe SERT [ 6 , 7 , 66 , 67 ]. These results indicate that the intestinal absorption of metformin is mediated at least partly by OCT3 and PMAT expressed on apical membrane of enterocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the deeper knowledge of the structure and function of OCTs brings us closer to more precise and efficient medical treatments 22,41,42 . Therefore, our structures provide a new starting point for rational drug development targeting OCT3 in the treatment of depression 22,50 , diabetes 11,12,51 , cardiac disease 10,15 , and cancer chemotherapy 19,39,52 .…”
Section: Discussionmentioning
confidence: 99%
“…The herein investigated genetic variants 10,12,[35][36][37][38][39][40] were mapped on the structure of OCT3 (Fig. 4a) and functionally characterized in vitro (Fig.…”
Section: Structure-function Analysis Of Oct3 Genetic Variantsmentioning
confidence: 99%